Pandangan Hukum Islam tentang Denda Akibat Pembatalan Pinangan (Khitbah) oleh Pihak Perempuan - Fathullah (Asy-Syari’ah : Jurnal Hukum Islam, 2019)
Khitbah or application or proposal is a preliminary or pre-marriage period between a man and a woman, as a first step before the two carry out the marriage contract, so that each knows the candidate. The sermon itself must still be answered “yes” or “no”. If it has been answered “yes”, then be the woman as “makhtubah” or the woman who is officially applied. In connection with this engagement in society there is a habit at the time of its implementation, the prospective bridegroom gives a gift such as jewelry, money, food and produce as a sign that someone really intends to continue the marriage stage. the consequences of giving the prize are different from giving in the form of dowry Giving a grant that is not halal withdraws the grant, if he gives a grant voluntarily (charity), not for compensation. While the grantor who still has the right to withdraw the grant, if the grant is given in return for something that will be received, but he does not get it. Keyword: Islamic Law, Khitbah, Islamic Law